Synergistic Enzyme Mixtures to Realize Near‐Complete Depolymerization in Biodegradable Polymer/Additive Blends. Issue 49 (8th October 2021) - DelRe, Christopher; Chang, Boyce; Jayapurna, Ivan; Hall, Aaron; Wang, Ariel; Zolkin, Kyle; Xu, Ting
Abstract: Embedding catalysts inside of plastics affords accelerated chemical modification with programmable latency and pathways. Nanoscopically embedded enzymes can lead to near‐complete degradation of polyesters via chain‐end mediated processive depolymerization. The overall degradation rate and pathways have a strong dependence on the morphology of semicrystalline polyesters. Yet, most studies to date focus on pristine polymers instead of mixtures that contain additives and other components despite their nearly universal use in plastic production. Here, additives are introduced to purposely change the morphology of polycaprolactone (PCL) by increasing the bending and twisting of crystalline lamellae. These morphological changes immobilize chain ends preferentially at the crystalline/amorphous interfaces and limit chain‐end accessibility by the embedded processive enzyme. This chain‐end redistribution reduces the polymer‐to‐monomer conversion from >95% to less than 50%, causing formation of highly crystalline plastic pieces, including microplastics. By synergizing both random chain scission and processive depolymerization, it is feasible to navigate morphological changes in polymer/additive blends and to achieve near‐complete depolymerization. The random scission enzymes in the amorphous domains create new chain ends that are subsequently bound and depolymerized by processive enzymes. Present studies further highlight the importance to consider how the host polymer's morphologies affect the reactions catalyzed by embedded catalytic species. Abstract : When enzymes with deep, narrow active sites are embedded inside of plastics, chain‐end‐mediated processive depolymerization is realized. However, polymer additives can induce bending in crystalline lamellae, which causes chain ends to preferentially segregate at the crystal/amorphous interface where they are inaccessible for enzyme binding. Synergistic enzyme mechanisms can be exploited to create new chain ends and facilitate near‐complete depolymerization.